MEDICAL AND SOCIAL ASPECTS OF SEXUALLY TRANSMITTED INFECTIONS IN ADOLESCENTS IN THE REPUBLIC OF SAKHA (YAKUTIA) - L. I. Petrova; N. V. Savvina; A. A. Maksimova (LLC "Diagnostics and Vaccines", 2017)
In order to develop health-improving interventions for the prevention of sexually transmitted infections (STIs), a comprehensive socio-hygienic study of various groups of adolescents and young people was conducted. The questionnaires were analyzed on the following main parameters: social and personal characteristics, level of awareness about sexual relations and about STIs. In the study, two groups were identified: 1 group (main) - adolescents with STIs, 2 group (comparisons) - healthy adolescents. The first information on the existence of sexual relations, 48.7% of adolescents from the main group received from older friends and peers. Among the adolescents in the comparison group, 14% had sexual contact. Those who love their family and want their future family to be similar to their parents were significantly more (9 times) in the comparison group than in the main group (20.0% vs. 2.2%, p <0.0001). Information on STIs, transmission routes, complications, prevention is available in 39.7% of STIs patients, and only 18.7% in the comparison group. The objective reasons for the formation of a low moral and cultural level are identified: education in incomplete and unfavorable families, lack of study and work, low level of awareness of STIs and questionable sources of knowledge on this issue.